Impact of E-Service Quality on Satisfaction with E-Learning Usage at PT LSP XYZ - Gagah Maulidin Amirul; Arman Hakim Nasution (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2024)
PT LSP XYZ is a company that operates in the field of professional certification, where currently professional certification participants are experiencing an increase and decrease in participants, especially in the aspect of e-learning development which has an impact on customer satisfaction. If this is not repaired immediately, the damage will impact the level of customer satisfaction. This research aims to combine expectations and reality regarding the services provided by the company to customers using the Servqual method and analyze the factors that influence customer satisfaction with LSP XYZ which can then be used as a basis for formulating recommendations to increase the level of customer satisfaction of LSP XYZ. and Structural Equation Modeling (SEM) analysis tools.